THE EFFECT OF ADDITION OF GREEN GLASS POWDER ON THE STRENGTH OF CONE BLOCK PRESSING - Rachmat Mudiyono (Reviews in Civil Engineering, 2020)
At this time the manufacture of products using waste has been developed. One of them is a cone block. In this study, the addition of green glass powder material will be carried out in order to determine the effect on the quality of the cone block. The addition of green glass powder aims to determine the difference in compressive strength against the conventional model cone block. The silica content contained in green glass powder is in the form of pozzolanic substances, a substance in the form of a cement-like content and can replace cement. This study modified the cone block with a mixture of green glass powder from a percentage of 8%, 10% and 15%.Penbased on previous research which states that the addition of more than 10% silica will affect the cone block structure. Tests carried out on cone blocks, namely the compressive strength test. The results of the cone block research on the compressive strength test, in general, the mixed cone block of 8%, 10% and 15% compressive strength decreased due to the slowing of the binding process due to the reduction of the cement element except for the cone block aged 14 days with a mixture percentage of 8% which had an increase.